MOTIF PERKULIAHAN NARAPIDANA DAN SIPIR LAPAS (Studi Fenomenologi Narapidana Dan Sipir Lapas Pada Perkuliahan Di Lapas Klas II A Pekanbaru Provinsi Riau) - Cutra Aslinda (UIR Press, 2018)
The purpose of the research is understand the motive of prisoner an prison officer class IIA and children prioner officer class IIB Also the officer of Kanwil kemenkum HAM of Riau Privince on lecture in Class IIA prison in pekan baru. The research approach which is isued is qualitative method with fenomenology subject. the subject of the research are prisoner, prison officers and the officer of kanwil kemenkum HAM of Riau province by purposive sampling. The data sampling was gathered through a deep interview and nonpartisipant observer a research literature study. The research reveal that the design is devided two. First, is for oriented motives to the past of themselves and the motives which oriented to the future.